2019
DOI: 10.3389/fimmu.2019.02308
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Functional Cure for Hepatitis B: The Rationale and Challenges for Therapeutic Targeting of the B Cell Immune Response

Abstract: The central role of the cellular immune response in the control and clearance of the hepatitis B virus (HBV) infection has been well-established. The contribution of humoral immunity, including B cell and antibody responses against HBV, has been investigated for a long time but has attracted increasing attention again in recent years. The anti-HBs antibody was first recognized as a marker of protective immunity after the acute resolution of the HBV infection (or vaccination) and is now defined as a biomarker f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 130 publications
(147 reference statements)
1
26
0
Order By: Relevance
“…A small numbers of the study cohort showed co-existence of HBs Ag/Hbs Ab reactive probably on a transitional state to clear the virus or probably suggesting a selection of immune escape mutants during the disease period, a finding previously reported. 32,[34][35][36][37] Individuals with immune tolerance CHBV could not be identified within the study cohort, in agreement with recent reports that challenged the early concepts of existence of this immune pathologic phase. Recent evidence showed that subtle liver damage in the presence of normal aminotransferases levels exits in CHBV individuals.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A small numbers of the study cohort showed co-existence of HBs Ag/Hbs Ab reactive probably on a transitional state to clear the virus or probably suggesting a selection of immune escape mutants during the disease period, a finding previously reported. 32,[34][35][36][37] Individuals with immune tolerance CHBV could not be identified within the study cohort, in agreement with recent reports that challenged the early concepts of existence of this immune pathologic phase. Recent evidence showed that subtle liver damage in the presence of normal aminotransferases levels exits in CHBV individuals.…”
Section: Discussionsupporting
confidence: 85%
“…Recent evidence showed that subtle liver damage in the presence of normal aminotransferases levels exits in CHBV individuals. 10,32,[34][35][36][37]…”
Section: Discussionmentioning
confidence: 99%
“… 1 The exact mechanism of how PEG-IFN promotes HBsAg clearance remains unknown, and studies on predictors of HBsAg loss are still in the exploratory stage. 9 11 However, there is accumulating evidence that PEG-IFN predominantly expands the NK cells compartment without boosting virus-specific T cells in HBV. 12 , 13 NK cells respond quickly to stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the function of HBV-specific B cells in HBV infection has been characterized by using fluorescently labeled HBV proteins, showing impairment in chronically infected patients (174)(175)(176). Modulation of B cell function and antibody production may represent another option for immunotherapy (87,177). A number of host genetic determinants have been identified to contribute to HBV control and pathogenesis (178).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%